Left neck and right biceps muscle vibrations have similar effects on perceived body orientation - Stammler, Britta; Karnath, Hans-Otto (Experimental brain research, 2025)
Vibrating muscles to manipulate proprioceptive input creates the sensation of an apparent change in body position. This study investigates whether vibrating the right biceps muscle has similar effects as vibrating the left posterior neck muscles. Based on previous observations, we hypothesized that both types of muscle vibration would shift the perception of healthy subjects’ subjective straight-ahead (SSA) orientation in the horizontal plane to the left. Such a finding would be extremely interesting for future treatment of spatial neglect, a disorder following right-sided stroke brain lesions. Twenty healthy participants (11 females, 9 males, aged 20–52) were tested under five conditions: baseline (no vibration), vibration of left neck muscles, vibration of right biceps with the arm fixed to the wall, vibration of right biceps with the arm lying on a table, and vibration of right triceps with the arm fixed to the wall. Participants had to align a laser pointer (by verbal instructions) with their perceived SSA position in complete darkness. ANOVA revealed significant SSA shifts with neck and biceps vibrations but not with triceps vibration. The largest leftward SSA shift occurred with right biceps vibration while the arm was lying on the table (-6.1°), followed by left neck muscle vibration (-6.0°), and right biceps vibration with the arm fixed to the wall (-5.4°). Post-hoc power analyses showed high power (> 0.98) for the significant differences compared to the baseline condition. The finding that right biceps vibration affects SSA perception similarly to left neck muscle vibration offers potential for clinical applications in treating spatial neglect. Future research should explore the therapeutic efficacy of vibrating the right biceps in neurological patients with spatial neglect.